(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
It is well known that the mosquito, Culex quinquefasciatus, badly affect individuals in endemic setting, causing filariasis. Intervention targeting the vector larva has not been given much priority. Therefore, the efficacy of ethanolic extract of Ageratum conyzoides, Bidens pilosa L. and Spilanthes filicaulis and a mixture of these plants in equal proportion was evaluated for larvicidal activities against filarial mosquito Culex quinquefasciantus. Phytochemical screening of the extracts was done by dissolving 5g each of plants in 30ml ethanol and water separately to obtain plant extracts. Samples were qualitatively screened following standard methodology for phytochemicals. Mortality of mosquito larva was examined after 12hrs, 24hr, 36hrs, and 48hrs treatment. Probit analysis for 50% Lethal Concentration was done using GraphPad Prism 9. Phytochemical screening of the plants revealed that Bidens pilos, Spilanthes filicaulis and Ageratum conyzoides contained moderated concentrations of Anthraquinones and Cardiac glycosids, Tannins, and Alkaloids respectively. Complete mortality was recorded with 0.60ml of Bidens pilosa, and Spilanthes filicaulis at 48hours and 36 hours respectively. More so, complete mortality was recorded with 0.40 and 0.60ml of the three plants in mixed proportion at 36 hours and 24 hours respectively. Larval mortality and time mortality were significantly (p<0.05) different. 50%Lethal Concentration for Ageratum conyzoides L, Bidens pilosa L, Spilanthes filicaulis, and mixture of the three plants in equal proportion are 0.33ml, 0.25ml, 0.08ml, and 0.06ml respectively. Results showed that these plant materials exhibit significant activity and could be considered as potent natural larvicidal agent.